A Spatial Analysis of Student Binge Drinking, Alcohol‐Outlet Density, and Social Disadvantages. (25th June 2013) - Lo, Celia C.; Weber, Joe; Cheng, Tyrone C.
<x xml:space="preserve">Abstract</x> Background and Objectives This paper examined whether and how student binge drinking at the individual level was influenced by population disadvantages, community instability, alcohol‐outlet density, and protective factors generated by community and school. Methods We used a dataset collected in 2002 by the Alabama Department of Mental Health, with additional materials generated by the 2000 Census and from the Alabama State Department of Education. School‐catchments were employed as geographic units of analysis. The final sample comprised 78, 138 public‐school students in grades 6–12 who attended schools located in the 566 school‐catchments. Results We hypothesized the presence of spatial processes that, once identified, would enhance understanding of student binge drinking. Our results confirmed that student binge drinking in a focal area was affected by that area's structural factors and also by individual‐level risk and protective factors. The results did not support the hypothesized impact of surrounding areas' characteristics on student binge drinking in the focal area. Conclusions and Scientific Significance The results of our study clearly indicate that both environment‐based factors and individual‐level risk and protective factors are important in explaining student binge drinking in Alabama. (Am J Addict 2013;22:391–401)